2017
DOI: 10.1021/acs.jafc.7b00048
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Viscosity of Superior and Inferior Spikelets of Japonica Rice with Various Percentages of Apparent Amylose Content

Abstract: Viscosity, a crucial characteristic for rice palatability, is affected by endosperm characters. We compared correlations between differences in viscosity of japonica rice with various palatability and endosperm characters. Changes in apparent amylose and protein contents (AAC% and PC%, respectively) and amylopectin side-chain distribution and the relationship of these traits with palatability were investigated in superior and inferior spikelets of good cultivars with low amylose content from Hokkaido and commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 28 publications
1
22
2
Order By: Relevance
“…Peak viscosity provides a measure of the extent to which starch granules swell in the presence of water, heat, and shear. Breakdown viscosity measures the resistance of starch to fragmentation during cooking and gives an indication of the ease of cooking as well as palatability (Ma et al, ). Setback viscosity, on the other hand, measures the ability of heated starch to recover its viscosity upon cooling and provides an indication of the texture of cooked rice.…”
Section: Introductionmentioning
confidence: 99%
“…Peak viscosity provides a measure of the extent to which starch granules swell in the presence of water, heat, and shear. Breakdown viscosity measures the resistance of starch to fragmentation during cooking and gives an indication of the ease of cooking as well as palatability (Ma et al, ). Setback viscosity, on the other hand, measures the ability of heated starch to recover its viscosity upon cooling and provides an indication of the texture of cooked rice.…”
Section: Introductionmentioning
confidence: 99%
“…AKI‐ dep1 exhibited significantly lower breakdown, higher final viscosity and setback values than those of AKI‐ DEP1 (Table ). Previous studies demonstrated that rice with high palatability has a higher breakdown and a lower final viscosity and setback than low‐palatable varieties (Ma et al, ). Thus, we inferred that AKI‐ dep1 showed lower palatability than that of AKI‐ DEP1 .…”
Section: Resultsmentioning
confidence: 98%
“…Elastic index and the overall quality of balance of rice decreased and increased, respectively. Ma et al (2017) also found that the accumulated density of starch in inferior grain was much lower compared with the superior grain. As the elasticity of the surface layer was smaller, and the stickiness and quality of balance were higher, the overall palatability of the superior grains improved greatly.…”
Section: Differences In Intergranular Texture Characteristics and Tmentioning
confidence: 85%
“…Xu, Li, Qian, Wang, and Yang (2016) compared the accumulation of starch granules between superior and inferior grains in japonica rice, wheat, and maize, and reported that the distribution ratio of large starch granules in inferior grain was higher than that in superior grain, which lead a large gap between the starch granules. Ma et al (2017) also found that the accumulated density of starch in inferior grain was much lower compared with the superior grain. Therefore, it can be concluded that, as the degree of grain filling is high, the starch granules are arranged closely, making conditions favorable for heat conduction, and thereby, the degree of gelatinization of the starch.…”
Section: Differences In Intergranular Texture Characteristics and Tmentioning
confidence: 85%